Relationships Quality of Diet in Pregnant Women With Baby Birth Weight - Syahda, Yosa Oktari (Majalah Kedokteran Andalas, 2023)
Objective : Writing this article in the form of a systematic literature review aims to analyze the relationships between food quality in pregnancy women and the baby's birth weight .Method : Systematic literature review method by taking 9 journals , namely 9 international journals according to the specified keywords criteria .Results : From the results of the literature review analysis of 9 journals , all journals found significant results between the quality of diet and the baby's birth weight .Conclusion : From this research it is concluded that there is a relationship between the quality of diet and birth weight . It is hopefully that this systematic literature review can become a reference for future researchers and that further research can be carried out on other birth outcomes